Determining Relative Competence in Resolving Criminal Defamation Cases Under Indonesian Positive Law - Josephine, Emeralda Janessa; Hutabarat, Rugun Romaida (Jurnal Ilmu Hukum Kyadiren, 2025)
The determination of relative competence in criminal cases is based on the court with geographical authority to adjudicate a particular case, as established through normative legal research. Relative competence is determined by the location where the crime occurred or the residence of the perpetrator and/or victim, as stipulated in Article 84 paragraph (1) of the Criminal Procedure Code: “The competent district court is the court where the crime was committed.” In the South Jakarta District Court Decision Number 283/Pid.Sus/2023/PN.Jkt.Sel, although the crime occurred in Bogor, the case was tried in the South Jakarta District Court. The judge considered additional factors, such as the defendant’s place of residence or the case’s significant influence in the area. This demonstrates flexibility in applying relative competence while adhering to relevant legal provisions.